Essential role of ATP6AP2 enrichment in caveolae/lipid raft microdomains for the induction of neuronal differentiation of stem cells - Makdissy, Nehman; Haddad, Katia; AlBacha, Jeanne D’arc; Chaker, Diana; Ismail, Bassel; Azar, Albert; Oreibi, Ghada; Ayoub, David; Achkar, Ibrahim; Quilliot, Didier; Fajloun, Ziad (Stem cell research & therapy, 2018)
Background The subcellular distribution of prorenin receptor and adaptor protein ATP6AP2 may affect neurogenesis. In this study, we hypothesized that ATP6AP2 expression and subcellular relocalization from caveolae/lipid raft microdomains (CLR-Ms) to intracellular sites may correlate with neuronal differentiation (Neu- Dif ) of adipose-derived mesenchymal stem cells (ADSCs). Methods Human ADSCs isolated from 24 healthy donors and 24 patients with neurological disorders (ND) were cultured and induced for Neu- Dif . The mechanism of action of ATP6AP2 and the impact of its localization within the plasma membrane (particularly CLR-Ms) and intracellular sites on several pathways (mitogen-activated protein kinase, Wnt(s) signaling and others) and intracellular calcium and exosome release were evaluated. The impact of CLR-Ms on ATP6AP2 or vice versa was determined by pharmacological disruption of CLR-Ms or siATP6AP2 assays. Results In patients with ND, loss of ATP6AP2 from CLR-Ms correlated with an inhibition of Neu- Dif and signaling. However, its relocalization in CLR-Ms was positively correlated to induction of Neu- Dif in healthy subjects . An apparent switch from canonical to noncanonical Wnt signaling as well as from caveolin to flotillin occurs concurrently with the increases of ATP6AP2 expression during neurogenesis. Stimulation by renin activates ERK/JNK/CREB/c-Jun but failed to induce β-catenin. Wnt5a enhanced the renin-induced JNK responsiveness. Gα proteins crosslink ATP6AP2 to caveolin where a switch from Gαi to Gαq is necessary for Neu- Dif . In ATP6AP2-enriched CLR-Ms, the release of exosomes was induced dependently from the intracellular Ca 2+ and Gαq. Pharmacological disruption of CLR-M formation/stability impairs both ATP6AP2 localization and Neu- Dif in addition to reducing exosome release, indicating an essential role of ATP6AP2 enrichment in CLR-Ms for the induction of Neu- Dif . The mechanism is dependent on CLR-M dynamics, particularly the membrane fluidity. Knockdown of ATP6AP2 inhibited Neu- Dif but increased astrocytic- Dif , depleted ATP6AP2/flotillin/Gαq but accumulated caveolin/Gαi in CLR-Ms, and blocked the activation of JNK/ERK/c-Jun/CREB/exosome release. siATP6AP2 cells treated with sphingomyelinase/methyl-β-cyclodextrin reversed the levels of caveolin/flotillin in CLR-Ms but did not induce Neu- Dif , indicating the crucial relocalization of ATP6AP2 in CLR-Ms for neurogenesis. Treatment of ND-derived cells with nSMase showed reversibility in ATP6AP2 abundance in CLR-Ms and enhanced Neu- Dif. Conclusions This study gives evidence of the determinant role of CLR-M ATP6AP2 localization for neuronal and oligodendrocyte differentiation involving mechanisms of switches from Gαi/caveolin/canonical to Gαq/flotillin/PCP, the ERK/JNK pathway and Ca 2+ -dependent release of exosomes and as a potential target of drug therapy for neurodegenerative disorders.